2019
DOI: 10.1186/s13256-019-2271-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after mumps: a case report

Abstract: IntroductionOophoritis, a complication of mumps, is said to affect only 5% of all postpubertal women. In this report, we present a case of a 31-year-old Iranian woman with amenorrhea and infertility due to an infantile uterus and atrophic ovaries associated with contracting mumps at a young age. She later successfully carried a healthy baby to term.Case presentationThe patient was diagnosed with oophoritis when she was 8 years of age. She had no menses before treatment. The patient underwent a low-dose contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Zika and mumps increased the rate of follicular cell apoptosis (4, 50), although this was not seen with HCV (53). Necrosis and hemorrhage were the major features of CMV oophoritis (11,(13)(14)(15)(16), while atrophic changes were the predominant feature of mumps (1,21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Zika and mumps increased the rate of follicular cell apoptosis (4, 50), although this was not seen with HCV (53). Necrosis and hemorrhage were the major features of CMV oophoritis (11,(13)(14)(15)(16), while atrophic changes were the predominant feature of mumps (1,21).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed fewer histopathological descriptions of mumps oophoritis than CMV oophoritis, although ovarian atrophy and sclerosis seem to be major features of this condition (Table 2) (1,21). In a woman with suspected in utero exposure to mumps, laparoscopy revealed an atrophic endometrium and sclerotic, atrophic ovaries that were approximately one-fourth the size of normal ovaries (1).…”
Section: Mumpsmentioning
confidence: 99%
See 3 more Smart Citations